Enhanced bioactivity of electrospun piezoelectric membranes with embedded micro and nano particles - Almeida, Sérgio Daniel Inácio (2022)
Bone tissue damage is a common health issue that tends to increase in severity with age and the existence of other underlying conditions. Nowadays the common practice for treatments requires insertion and extraction surgeries of supports such as screws and plates, adding to the risk of a second surgery. Functional biomaterials intend to eliminate this added risk while also enhancing the functionality of implants, either by accelerat- ing the regenerative process or augmenting other useful properties. Piezoelectricity is present in bone tissue and plays a major role in the regenerative process of fractures and healing of eventual defects, using Polyvinylidene Fluoride (PVDF) and Barium Titanate (BaTiO3) both well-known biomaterials with a piezoelectric phase being a polymer and a ceramic respectively. These types of materials have potential applications for hard tis- sue regeneration and engineering, as the piezoelectric effects stimulate osteogeneses and osseointegration. This project developed piezoelectric PVDF membranes embedded with piezoelectric BaTiO3 particles as a tool for taking advantage of the piezoelectric mechanism inherent in bone tissue regeneration to accelerate the healing process. To achieve this, the mem- branes were produced by electrospinning onto a rotating drum to promote the alignment of fibers, and commercially available particles were used while attempting a novel sol-gel synthesis method using barium acetate and titanium(III) chloride as precursors while using cell culture medium to stabilize particle growth. Electrospinning was the chosen method for producing the membranes, as it allows the formation of a structure favoring cell growth and adhesion and promotes the formation of the piezoelectric phase and polar- iation of PVDF. After defining the best parameters for producing pure PVDF membranes, the process was repeated for the BaTiO3 embedded membranes. The membranes and particles were characterized by severeal techniques, as well as the precursor materials, and the bioactivity and cytotoxicity of the final membranes were also investigated.